La peste come paradigma. Il medioevo in “Storia delle epidemie” di Frank M. Snowden - Tommaso Duranti (Storicamente)
The scientific and historiographical debate about the pathological identity of the three plague pandemics is now apparently closed. New frontiers opened up by palaeogenetics allows a chronological reassessment, a global overview and a reinterpretation of the past that was unimaginable a few decades ago. But can the history of diseases be limited to a natural history oriented solely by current microbiological and epidemiological criteria? The chapters dedicated by Frank Snowden to the medieval plague allow us to reflect further on the methodology and purpose of historiography on diseases and their diverse consequences, not forgetting that a disease is also a cultural factor.